2015
DOI: 10.1039/c5an00260e
|View full text |Cite
|
Sign up to set email alerts
|

Enantioseparation characteristics of tadalafil and its intermediate on chitin derived chiral stationary phases

Abstract: Due to the low solubility and swelling properties of chitin bis(arylcarbamate) in most organic solvents, the chiral stationary phases (CSPs) prepared from chitin derivatives can be analyzed with a wide range of solvents. In order to develop new CSPs of chitin derivatives with halogen groups, chitin was derivatized with three different phenyl isocyanates to obtain chitin bis(4-trifluoromethoxyphenylcarbamate), chitin bis(3-chloro-4-methylphenylcarbamate) and chitin bis(4-chloro-3-trifluoromethylphenylcarbamate)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…Eluent: (A) n‐hexane/ethanol (80:20, v/v) and (B) n‐hexane/ethanol (90:10, v/v). Reproduced with permission from …”
Section: Chitosan Derivatives As Chiral Stationary Phases For Hplcmentioning
confidence: 99%
See 1 more Smart Citation
“…Eluent: (A) n‐hexane/ethanol (80:20, v/v) and (B) n‐hexane/ethanol (90:10, v/v). Reproduced with permission from …”
Section: Chitosan Derivatives As Chiral Stationary Phases For Hplcmentioning
confidence: 99%
“…More systematic studies including the influence of substituents and the tolerance to various organic solvents on the enantioseparation of many novel CSPs based on chitosan derivatives using highly deacetylated chitosan as a starting material have been reported by the Bai group. For example, a series of chitosan alkyl amide and alkyl urea derivatives were prepared upon introducing an alkyl group, such as cyclobutyl [27], isobutyryl [28][29][30], n-octyl [31] and n-pentyl [32], at the 2-position of chitosan, and the chiral recognition ability and the solvent tolerance of these chitosan derivatives bearing the same phenylcarbamate groups at the Reproduced with permission from [26] 3-and 6-position investigated ( Figure 2). It was observed that the chiral recognition performance of these coated-type CSPs was significantly influenced by the nature (e.g., electronwithdrawing and electron-donating properties), position, and number of substituents on the phenyl moieties of the chitosan derivatives and the eluent's composition.…”
Section: Chitosan Derivatives As Chiral Stationary Phases For Hplcmentioning
confidence: 99%
“…Following the same strategy, and aiming the enantioseparation of tadalafil and its intermediates, Zhang et al, synthesized new chitin bis-arylcarbamates, specifically chitin 3-chloro-4-methyl-(18), 4-trifluoromethoxy-(19) and 4-chloro-3-trifluoromethyl- (20) phenylcarbamates (Table 1) [56]. The three chitin derivatives were coated on macroporous 3-aminopropyl silica and the obtained CSPs were successful in the enatioresolution of all tested analytes [56].…”
Section: Chitin-based Cspsmentioning
confidence: 99%
“…The best chromatographic result was achieved for flavanone with α and Rs values of 4.70 and 4.33, respectively, using a mixture of hexane/2-propanol 80:20 as mobile phase [65]. In recent studies (2016), Tang et al, prepared several bis-phenylcarbamate derivatives in which the amine moiety of chitosan was modified by an isobutyrylamide moiety (46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) [66,67]. The synthesized chitosan derivatives were coated on aminopropyl silica resulting in a series of new CSPs for LC.…”
Section: Chitosan Bis-carbamate Cspsmentioning
confidence: 99%
“…Moreover, there is a helix in chitin suprastructure , and this structural feature is critical for polysaccharide derivatives to exert the function in chiral separation . Thus, chitin and chitosan were once derivatized and the resulting products were used as chiral selectors for chiral stationary phases (CSPs) . In addition, according to the reports , carbamylated chitin/chitosan derivatives are difficultly dissolved in common organic solvents, thus possibly being highly tolerable to mobile phases that consist of various organic solvents.…”
Section: Introductionmentioning
confidence: 99%